Văn học Việt Nam thế kỷ XX - Phan, Cự Đệ (Văn học, 2004)
Giới thiệu truyện ngắn của nhiều tác giả:Võ Huy Tâm, Nguyễn Thị Cẩm Thạnh, Nguyễn Quang Thân, Bùi Bình Thi, Nguyễn Đình Thi, Nguyễn Thi, Xuân Thiều, Bích Thuận